La bande dessinée revendicative et mémorielle de Carlos Giménez - Pierre-Alain de Bois (Cahiers de Civilisation Espagnole Contemporaine)
This article focuses on the Spanish cartoonist Carlos Giménez, and offers an analysis of three of his main "protest and memorial" works, Paracuellos, Barrio and 36-39: Malos Tiempos. The study will show how Carlos Giménez used this sequential art of comics to put into words and images painful memories related to the Spanish Civil War and its consequences, and how, over time, the author went from a writing of the denunciation to a writing of the memory, that it seems to want to transmit today to the future generations.